Serum levels of galactose-deficient immunoglobulin (Ig) A1 and related immune complex are associated with disease activity of IgA nephropathy - Suzuki, Yusuke (Springer Japan, 2014)
BACKGROUND: The primary abnormal manifestation in immunoglobulin A nephropathy (IgAN) is recurring bouts of hematuria with or without proteinuria. Although immunohistochemical analysis of renal biopsy tissue remains the gold standard not only for diagnosis but also for evaluating the activity of IgAN, new sensitive and reasonably specific noninvasive tests are emerging to guide therapeutic strategy applicable to all stages of IgAN. The present study examined serum levels of galactose-deficient IgA1 (Gd-IgA1) and its immune complex (IgA/IgG-IC) as noninvasive markers for the disease activity. METHODS: We enrolled 50 IgAN patients (male 40 %, median age 37 years) showing complete or partial clinical remission after steroid pulse therapy with tonsillectomy (TSP) whose clinical data and serum could be followed up for 3–5 years. RESULTS: Cross-sectional analysis revealed that the degree of hematuria and proteinuria were significantly associated with levels of Gd-IgA1 and levels of IgA/IgG-IC. Longitudinal analysis further showed that from the group of 44 patients with heavy hematuria before TSP, 31 patients showed complete disappearance of hematuria (group A), but the remaining patients did not (group B). Although the levels of Gd-IgA1 and IgA/IgG-IC in the two groups before TSP were similar, percentage decrease of Gd-IgA1 and IgA/IgG-IC levels in group A was significantly higher than in group B. CONCLUSION: Disease activity of IgAN assessed by hematuria and proteinuria correlated with serum levels and changes of Gd-IgA1 and IgA/IgG-IC. These new noninvasive disease activity markers can be useful for future activity scoring system and guiding therapeutic approaches.